ОСОБЕННОСТИ СУТОЧНОГО ПРОФИЛЯ АРТЕРИАЛЬНОГО ДАВЛЕНИЯ И АРТЕРИАЛЬНАЯ РИГИДНОСТЬ У БОЛЬНЫХ ГИПЕРТОНИЧЕСКОЙ БОЛЕЗНЬЮ, ОСЛОЖНЁННОЙ ИШЕМИЧЕСКИМ ИНСУЛЬТОМ - М. В. Беззубцева; Н. Н. Прибылова; А. Е. Бирюков (Архивъ внутренней медицины, 2014)
The arterial hypertension complicated by development of a brain stroke is one of the main reasons of population disability. In the article there are presented features of circadian blood pressure profile and arterial stiffness at patients with an ischemic stroke with uncorrected arterial hypertension. It is established that the increased variability of arterial pressure, pulse wave velocity and central aortal pressure are starting factors of ischemic stroke development and these parameters may be used as predictive indicators of a functional outcome of acute ischemic stroke.